Numerical investigation on the coupling of ash deposition and acid vapor condensation on the H-type fin tube bank. (5th July 2018) - Wang, Y.C.; Tang, G.H.
Highlights: Particle deposition is studied with combined acid vapor condensation and fly ash deposition. Factors of particle diameter, flue gas velocity, acid vapor content and tube bank are considered. Distribution and deposition mass of low temperature bonding ash and loose ash are discussed. The low temperature bonding ash is largest on the first row tube in in-line tube bank. Loose ash is largest on the third row in staggered tube bank. Abstract: There usually occurs a serious fouling on the heating surface of the low temperature economizer in boilers. The deposited ash on the surface could cause clogging and corrosion of the heat exchanger and even result in serious safety incident. Especially the low temperature bonding ash will corrode the surface severely. The distributions of the low-temperature bonding ash and the loose ash on the surface are numerically simulated in this study based on the theory of the particle transportation model, particle deposition model, force analysis of the particle and the acid point temperature model. The effect of fly ash particles on the content of the acid vapor in the flue gas is considered. Various factors on the distribution of deposited ash are investigated including the particle diameter, flue gas velocity, content of the acid vapor and the tube bank arrangement. The low temperature bonding ash is the largest on the first row tube in the in-line tube bank. However, both modes of deposited ash are largest on the third row tube in the staggered tube bank and they are difficult to remove.